Internal Control over Financial Reporting and Resource Extraction: Evidence from China* - Ge, Weili; Li, Zining; Liu, Qiliang; McVay, Sarah (Contemporary Accounting Research, 2021)
ABSTRACT We examine whether the strength of internal control over financial reporting (internal control) reduces the expropriation of resources from the firm by managers and controlling shareholders. Although we have ample evidence from prior literature that internal controls reduce errors in financial reports, it is less clear that they can curb resource extraction, because management may fail to enforce these controls. Exploiting the setting of China, where we have a rich internal control data set and established measures of resource extraction, we provide evidence consistent with internal controls curbing resource extraction on average. In particular, we document a negative association between internal control strength and resource extraction. We also find that the association between internal control strength and resource extraction is weaker in settings where we expect management to have fewer incentives to enforce these controls: within state‐owned firms and within non‐state‐owned firms that have a powerful controlling shareholder. We interpret these results as suggesting that internal controls must both exist and be enforced by management for the controls to safeguard assets. Although the analyses are conducted using Chinese data, we expect the spirit of our findings to generalize to other settings—management can “window dress” internal control procedures while still engaging in undesirable behavior.